The Analysis on The Formulation of Integrated Pest Management Policy Strategy by Using Swot-AHP Method (A Case Study on Vegetable Plant Cultivation in Lampung Province) - Sudiono Sudiono; Soerjono Hadi Sutjahyo; Nurheni Wijayanto; Purnama Hidayat; Rachman Kurniawan (Politeknik Pertanian Negeri Payakumbuh, 2019)
The objective of this research was to formulate a policy strategy for integrated pest management by using SWOT AHP methods (case study on vegetable cultivation in Lampung Province). This method used A’WOT; the combination of AHP (Analytical Hierarchy Process) analysis and SWOT (Strength-Weakness-Opportunity-Threat) analysis. The analysis result showed the main strength factors becoming the base for sustainable agricultural business were the availability of good structures and infrastructures both in production and marketing, and the availability of sufficient production structure (seeds) with good quality and quantity. The weakness factors becoming concern were dominantly lack of institutional funding (capital) for vegetable business, many problems in the integrated pest management (IPM) technology implementation stage, many problems in good agriculture practices (GAP), and numbers of families making their life as farmers. The opportunity factors were the availability of IPM and GAP technologies, growing campaign for consuming domestic products reducing import, and high government commitment to improve vegetable farmers’ welfare. The threats to concern were no protection operational base and farmer’s empowerment, very few institutional funding (capital) for vegetable business, and many problems in the GAP and technology implementation. Six strategies becoming priority in order were drafting the regulation and standard of operation that regulate IPM and GAP implementations; strengthening farmer’ institution, capital and agricultural insurance; drafting legality of operational protection and farmer’s empowerment; agricultural intensification in order to improve quantity, quality, safety, and environmental insight for food security and independency; optimization of technology transfer by socialization or education of IPM and GAP for vegetable crops; and inexpensive IPM system based controlling technology development and effective and efficient of alternative production structures.